2003
DOI: 10.1007/s101940300003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of migraine

Abstract: In the last decade, there have been many studies on epidemiology of migraine. These studies have dealt not only with those aspects that are strictly related to the spread of the disease, such as prevalence and incidence rates, but also with other interesting aspects, such as familial occurrence, comorbidity and disability.In this paper, we deal with migraine incidence and above all with migraine prevalence, but we try to go beyond sheer data and percentage figures in order to provide an in-depth analysis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…The female dominance is also seen in migraine with aura. In prevalence studies performed after 1988 it reaches a prevalence of 1.2-3.7% in men and 2.6-10.8% in women [67]. In contrast to menstrual migraine, migraine with aura occurs more frequently with high estrogen levels [68].…”
Section: Resultsmentioning
confidence: 99%
“…The female dominance is also seen in migraine with aura. In prevalence studies performed after 1988 it reaches a prevalence of 1.2-3.7% in men and 2.6-10.8% in women [67]. In contrast to menstrual migraine, migraine with aura occurs more frequently with high estrogen levels [68].…”
Section: Resultsmentioning
confidence: 99%
“…In a Swedish study by Linde and Dahlof (2004), only 45% of self-identified migraineurs had seen a health care provider for diagnosis of their migraines. Manzoni and Torelli (2003) and Lipton and Bigal (2005) reviewed the literature to identify the incidence of migraine, finding only four relevant studies. All of these were conducted between 1991 and 1996 (Breslau, Chilcoat, & Andreski, 1996;Rasmussen, 1995;Stang et al, 1992;Stewart, Linet, Celentano, Van Natta, & Ziegler, 1991).…”
Section: Epidemiology Of Migraine Disordermentioning
confidence: 99%
“…All of these were conducted between 1991 and 1996 (Breslau, Chilcoat, & Andreski, 1996;Rasmussen, 1995;Stang et al, 1992;Stewart, Linet, Celentano, Van Natta, & Ziegler, 1991). Incidence rates varied widely between the studies, ranging from 1.5 to 2 per 1,000 person-years for men and approximately 3 to 6 per 1,000 person-years for women about thE author (Manzoni & Torelli, 2003). However, these studies only examined the incidence of migraines in men and women younger than 30.…”
Section: Epidemiology Of Migraine Disordermentioning
confidence: 99%
“…It is estimated that approximately one-fi fth of women and one-tenth of men suff er from migraine of one or other type (Manzoni, 2003). In addition to throbbing pain in the eye or orbit, migraine patients may have nausea and are light and sound sensitive.…”
mentioning
confidence: 99%